2002
DOI: 10.1002/1521-3900(200206)182:1<119::aid-masy119>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Continuous precipitation polymerization of vinylidene fluoride in supercritical carbon dioxide: molecular weight distribution

Abstract: The surfactant‐free precipitation polymerization of vinylidene fluoride (VF2) in supercritical carbon dioxide was studied in a continuous stirred autoclave. The polymerization temperature ranged from 65 to 85°C, the average residence time in the reactor varied from 10 to 50 min., and the pressure was between 210 and 305 bar. Diethyl peroxydicarbonate was used as the initiator. The fractional conversion of monomer varied from 7 to 26%, the number‐average molecular weight of the polymer was between about 14,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…DeSimone and Howdle have reported independently that the increased reaction pressure increases the molecular weight and polydispersity of PVDF polymerized in sc-CO 2 by both the continuous process and the batch process [13,[27][28] . The reason might be proposed as following: the activation volume is negative during the polymerization reaction of VDF in sc-CO 2 according to the transition-state theory [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…DeSimone and Howdle have reported independently that the increased reaction pressure increases the molecular weight and polydispersity of PVDF polymerized in sc-CO 2 by both the continuous process and the batch process [13,[27][28] . The reason might be proposed as following: the activation volume is negative during the polymerization reaction of VDF in sc-CO 2 according to the transition-state theory [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Second, the possible occurrence of chain transfer to polymer has been ignored. However, the uncertainty in the experimental MWDs for PVDF also may contribute to the differences between the model and the data (Saraf, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In subsequent papers, the same group analyzed the effect of the reaction conditions on the average molecular weights. Specifically, they investigated the impact of the inlet monomer concentration, the residence time, the agitation rate, and the temperature.…”
Section: Vdf Polymerization: Literature Reviewmentioning
confidence: 96%
“…One factor that can help to elucidate the reactive sites of the polymerization is the equilibrium sorption of VDF/CO2/PVDF. Some studies showed that the concentration of VDF in PVDF is very low in the presence of scCO 2 (P < 100 bar), therefore very low rate polymerization in polymer phases can be expected, which justifies the choice of using a one‐phase reaction.…”
Section: Vdf Polymerization: Literature Reviewmentioning
confidence: 99%